A diversity-oriented synthesis of polyheterocycles via the cyclocondensation of azomethine imine. (19th August 2019) - Ansari, Arshad J.; Pathare, Ramdas S.; Kumawat, Anita; Maurya, Antim K.; Verma, Sarika; Agnihotri, Vijai K.; Joshi, Rahul; Metre, Ramesh K.; Sharon, Ashoke; Pardasani, R. T.; Sawant, Devesh M.
Abstract : Pd-Catalyzed sequential reactions to afford skeletally diverse molecules are described. Abstract : Pd-Catalyzed sequential reactions to afford skeletally diverse molecules are described. The reaction involved azomethine imine formation and a cyclocondensation reaction as individual steps. The methodology provides excellent regio- and stereocontrol. Skeletal diversity was ensured by changing the electrophilic counterpart of azomethine imine. Due to its broader diversity and complexity, the DOS methodology is likely to benefit drug discovery and development in the future.